Pelvic rhabdomyosarcoma causing urinary obstruction - Harinthiran V; Zubaidah S; Mohd Shahrulsalam Ms; M.R. Hassan; Ruzaimie Noor; M.N. Tarmizi (Elsevier, 2021)
Introduction: This is a unique and rare case of a huge pelvic tumour in a child whom primarily presented as acute urinary retention and haematuria after a fall. Case report: A 4 y-o child presented to casualty as he was not able to pass urine and was having dysuria for 1 day. Examination showed suspicious suprapubic mass which is likely to the urinary bladder. Bedside ultrasound showed the mass was likely to be the bladder. Further workup by Computer tomography showed large heterogenous solid mass arising from the pelvic cavity extending to lower abdomen measuring 6 × 11 × 9cm (APxWxCC). We performed laparotomy and debulking of the pelvic tumour. Intra-operatively we found the tumour to be gelatinous and friable. The tumour was removed in piecemeal. The overall histopathological features are consistent with embryonal rhabdomyosarcoma. Discussion: Rhabdomyosarcoma is a malignant mesenchymal tumour with skeletal muscle differentiation. The subtypes include embryonal(20%), alveolar(20%), and pleomorphic(20%) (Vinay Kumar and Aster, 2018) [1]. RMS in a paediatric age group accounts for almost 3.5% of cancer cases for children between 0 and 14. Rhabdomyosarcoma is a malignant mesenchymal tumour with skeletal muscle differentiation. The subtypes include embryonal(20%), alveolar(20%), and pleomorphic(20%) (Vinay Kumar and Aster, 2018) [1]. RMS in a paediatric age group accounts for almost 3.5% of cancer cases for children between 0 and 14. Conclusion: Rhabdomyosarcoma has a good overall survival prognosis with approximately 70% of patients 5 years after diagnosis.